LiNi0.5Mn1.5O4 synthesized through ammonia-mediated carbonate precipitation. (10th September 2015) - Gu, Yi-Jie; Li, Yu; Fu, Yang; Zang, Qing-Feng; Liu, Hong-Quan; Ding, Jian-Xu; Wang, Yan-Ming; Wang, Hai-Feng; Ni, Jiangfeng
Abstract: We synthesized LiNi0.5 Mn1.5 O4 cathode materials by using ammonia-mediated carbonate precipitation, and we studied how the ammonia concentration during synthesis (0.1–0.5 mol/L) affected the structural, physicochemical, and electrochemical characteristics of the prepared materials. X-ray diffraction and Rietveld refinement reveal that the amount of Li/Ni antisite defects in the LiNi0.5 Mn1.5 O4 depend much on the ammonia concentration. The LiNi0.5 Mn1.5 O4 prepared at 0.3 mol/L has the fewest Li/Ni antisite defects. This sample also delivers the best electrochemical performance, retaining a capacity of 133.5 mAh g −1 after 20 cycles at 0.1 C. Electrochemical impedance spectroscopy confirms that the LiNi0.5 Mn1.5 O4 prepared at 0.3 mol/L has lower charge transfer resistance, correlating with its better ion diffusion kinetics than the other materials.